Medication-precipitated Seizure in Psychiatric Patients: Typical vs. Atypical Antipsychotics - Shafti, Saeed S. (Current Psychopharmacology, 2020)
Backgrounds: It is unknown whether second-generation antipsychotics are safer than first-generation antipsychotics in terms of seizure induction. Objective: In the present assessment, the relationships between the incidence of seizure attacks among a great sample of non-western psychiatric inpatients and prescribed typical and atypical antipsychotics have been probed and analyzed based on the existing data in the literature. Methods: Razi psychiatric hospital, as one of the largest and oldest public psychiatric hospitals in the Middle East, had been selected as the field of study in the present retrospective estimation. For assessment, all inpatients that had suffered a seizure during the last sixtyfour months had been included in the current study. Results: Among seventy-four patients who had experienced seizure attack during the inpatient management, and had been prescribed antipsychotics for symptomatic management of primary psychiatric disorders, 67.56% had received atypical antipsychotic and the remaining (32.43%) had received typical antipsychotics, which revealed a significant quantitative difference between them (p<0.000). Among atypical antipsychotics, olanzapine was the most recommended antipsychotic (33.78%), followed by risperidone (34%), quetiapine (9.45%), and clozapine (n=1, 1.35%). Among typical antipsychotics, too, haloperidol (28.37%) was significantly more prescribed than chlorpromazine (2.70%) and thioridazine (1.35%) (p<0.000). By the way, there was no significant difference, quantitatively, between olanzapine and haloperidol in the present evaluation (p<0.47). Conclusion: Atypical antipsychotics have comparable potentiality, as typical antipsychotics, for triggering seizure attacks, which demands indispensable cautiousness by clinicians when prescribing such a group of medications for epileptic and neuropsychiatric patients.
Keywords: typical antipsychotic